Ancient Greek Literary Letters - Rosenmeyer, Patricia A. (Routledge Classical Translations, 2006)
The first referenece to letter writing occurs in the first text of western literature, Homer's Iliad. From the very beginning, Greeks were enthusiastic letter writers, and letter writing became a distinct literary genre. Letters were included in the works of historians but they also formed the basis of works of fiction, and the formal substructure for many kinds of poem. Patricia Rosenmeyer, an authority on the history of the Greek letter, assembles in this book a representative selection of such 'literary letters', from Aelian and Alciphron to Philostrartus and the supposed letters of Themistocles. The book will be valuable for all students of Greek literature especially those studying Greek (and Latin) letter.